Teminat amaçlı alacağın temliki - Şafak, Ali (My University, 2010)
Teminat amaçlı alacağın temliki kurumunun pozitif hukukumuzda düzenlenmeyişi ve fakat uygulamada çok geniş yer tutması, işlemin uygulanışı ile ortaya çıkan sorunlara ilişkin öğretinin de görüş birliği içinde olmayışı bizi bu konuda çalışmaya iten başlıca etkenler olmuştur. Çalışmamız, giriş, üç ana bölüm ve sonuçtan oluşmaktadır. Konuya giriş yapıldıktan sonra, birinci bölümde konunun zeminini oluşturan inançlı işlem tanımı yapılmış, görünüş biçimleri saptanmış, benzer kavramlar ve bunları ayıran özellikler üzerinde durulmuştur. İkinci bölümde ise ana konuya girilerek, teminat amaçlı alacağın temliki kavramının tanımı, hukuki niteliği, tercih edilme sebepleri, diğer teminatlar arasındaki yeri, görünüş biçimleri, konusu, işlemin temel yapısı ele alınarak, işleme uygulanacak hükmümler tespit edilmiştir. Üçüncü bölümde ise tarafların hak ve borçları net olarak tespit edilmiş, teminat amaçlı alacağın temliki ilişkisini sona erdiren haller ve bunlara bağlanan hukuki sonuçlar ele alınmıştır. Sonuç bölümünde ise çalışmamız sonucunda elde ettiğimiz sonuçlar ve katıldığımız görüşler

halinde sunulmuştur. Alacak, teminat, devir, inançlı işlem. TRANSFER OF CLAIMS AS A GUARANTEE Ali ŞAFAK ABSTRACT The fact that organization of transfer of claims as a guarantee is not arranged in the our positive law and however that it has a wide coverage in the implementation and the fact that the implementation of process and the doctrine regarding the emerging problems are not in agreement have became the main factors which made us study on this subject. Our study comprises introduction, three main sections and conclusion. After introducing the subject, the definition of fiduciary process that forms the base of the subject is made in the first section, the view patterns were determined and similar conceptions and the features which distinguish them were emphasized. In the second section, the introduction to main subject was made and the definition of transfer of claims as a guarantee, the legal qualification and the preference reasons, its position among other guarantees, view patterns, subject, the basic structure of the process were discussed and the provisions that will be applied to the process was determined. In the third section, the rights and the debts of the parties were determined in a net way and the circumstances which terminate the relation of transfer of claims as a guarantee and the legal results related with them were discussed. In the conclusion part, the results that we obtained at the end of our study and the opinions that we agree with were presented in summary. Key Words: Receivable, guarantee, transfer, fiduciary process.
Keywords: Hukuk; Özel Hukuk; Teminat